Biophysical Control on Variability in Phytoplankton Production and Composition in the South-Western Tropical Indian Ocean During Monsoon 2014 - Tripathy, Sarat C.; Sabu, P.; Patra, Sivaji; Naik, Ravidas K.; Sarkar, Amit; Venkataramana, Vankara; Kerkar, Anvita U.; Sudarsanarao, Pandi (Frontiers in Marine Science, 2020)
The existing oligotrophic conditions in the southwest tropical Indian Ocean (SWTIO) is believed to be one of the causes for low phytoplankton productivity (PP) observed in this area. Though many remote sensing based studies on PP have been carried out in SWTIO; studies on in situ estimation of PP and its cause(s) of variability are scarce. Thus, to understand the controlling environmental forcings on the variability in phytoplankton biomass (chlorophyll-a; Chl-a), community structure and productivity, time series (TS; @6h intervals for 10 days) plus point measurements (RT) were carried out in the SWTIO during southwest monsoon (June) of 2014. Strong thermohaline stratification resulted in shallow (35-40m) mixed layer (ML). Subsurface Chl-a maximum (SCM) was observed to oscillate within 40-60m with majority of peaks at ~50m, and existed just beneath the ML depth. Light availability at the time of sampling was highly conducive for algal growth; whereas nutrient ratios indicated N- and Si-limitation suggesting unfavourable conditions for diatoms and/or silicoflagellates growth within the ML. Furthermore, HPLC-based pigments analysis confirmed dominance of nano-sized plankton (53%) followed by pico-plankton (25%) and micro-plankton (22%). Column integrated production (IPP) varied from 176 - 268 (241+43 mgC m-2 d-1) and was relatively stable during the observation period, except a low value on 11-June, which was ascribed to the drastic dropdown in the daily incident PAR due to overcast sky. Vertical profiles of PP and Chl-a resembled each other and maximum PP usually corresponded with SCM depths. The Chl-a-specific PP (PB) was mostly higher within the ML and showed no surface photoinhibition, due to the dominance of smaller phytoplankton (less prone to pigment packaging effect) in the surface layer. Comparatively, higher PB within the ML is indicative of phytoplankton healthiness during the sampling time, whereas low PB below the SCM was due to light limitation. Highest integrated Chl-a (39 mg m-2) and IPP (328 mgC m-2 d-1) observed at RT-2 was clearly linked to low sea surface height anomaly (SSHA), cyclonic disturbance and associated positive Ekman pumping. Conversely, high SSHA and strong stratification conditions prevailed at TS, RT-4 and RT-6 stations leading to comparatively low IPP.